Production of virus-free plant propagation material from infected nectarine trees - Economou, Athanasios Sotirios; Boubourakas, I.N.; Manganaris, George A. (My University, 2003)
Plum pox virus (PPV) is one of the major and common diseases in stone-fruit trees. The effect of thermotherapy in PPV-infected nectarine plants (Prunus persica var. nectarina Max, cv. Arm King) and plant regeneration from meristem-tip explants, as well as use of a reliable RT-PCR that detects extremely low virus titre of PPV in in vitro cultures were studied. Three weeks of thermotherapy at a maximum temperature of 35°C gave tender explants that used for meristem-tip culture. Meristem-tip explants first were established on WPM free of growth regulators and then for multiple shoot were subcultured on WPM supplemented with 8 µM BA and 0.8 µM IAA. Individual shoots produced from such meristem-tip cultures were tested for PPV presence with RT-PCR and gave ‘negative’ results (virus-free) at a frequency of 82.8%. Rooted in vitro microcuttings, derived from virus-free cultures, were established in the greenhouse conditions successfully.
Keywords: Peach; Plant propagation; Meristems; Polymerase chain reaction